Bronchogenic Cyst in a young Child - Bhattarai, Niraj; Shrestha, Rasesh; Thakur, Binay (Nepalese Journal of Cancer, 2022)
Bronchogenic cysts are rare cystic disease of the mediastinum in children. They are often asymptomatic and are diagnosed incidentally. Symptoms, if present are due to compression of the adjacent structures or the added infection. A 5 year old female child was referred to our thoracic surgery department with history of fever for 2 days. She had recurrent respiratory tract infection in the past needing treatment. CT revealed a cystic mass in the mediastinum. Video Assisted Thoracoscopic Surgery (VATS) excision of the cyst was done. The patient recovered uneventfully and the histopathological examination revealed it to be a bronchogenic cyst.